2020
DOI: 10.1111/jcmm.15687
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic gene signature based on an immunogenomic infiltration analysis of osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumour predominantly occurring in children and adolescents with a high tendency of local invasion and early metastases. Currently, the systemic chemotherapy plus wide surgical resection are generally recognized as the most effective therapy for this malignancy. However, the main protocol has not been improved since 1980s. And neither does the cure rate. The investigations of prognostic factors and biomarkers of cancer and sarcoma are in progress for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In this study, we find that infiltration of CD8 T cells, NK cells and M1 Macrophages have a positive association with prognosis, while infiltration of γδ T cells, Mast cells, M0 Macrophages and Dendritic cells have a negative association with prognosis. Yu et al [ 24 ] also illustrates that high level of CD8 T cells is a good prognosis in their survival analysis, and results from [ 26 ] and [ 28 ] indirectly suggest the positive prognostic value of CD8 T cells. Tang et al [ 26 ] reports that CD8 T cells infiltration has a positive correlation with CXCR3 expression which is related to good prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we find that infiltration of CD8 T cells, NK cells and M1 Macrophages have a positive association with prognosis, while infiltration of γδ T cells, Mast cells, M0 Macrophages and Dendritic cells have a negative association with prognosis. Yu et al [ 24 ] also illustrates that high level of CD8 T cells is a good prognosis in their survival analysis, and results from [ 26 ] and [ 28 ] indirectly suggest the positive prognostic value of CD8 T cells. Tang et al [ 26 ] reports that CD8 T cells infiltration has a positive correlation with CXCR3 expression which is related to good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another set of studies find genes with prognostic values by applying Cox model on survival data or performing differentially expressed genes analysis between two groups of interest, and then investigate the relationship between these genes and estimated immune infiltrates [ 26 30 ]. Others study the association of immune abundance with clinical information directly [ 24 , 31 34 ]. Our work falls somewhat into the third category.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more and more studies are involved. For example, in the nine studies (Cao et al, 2020;Chen Z. et al, 2020;Song et al, 2020;Wen et al, 2020;Xiao et al, 2020;Yu et al, 2020;Zhu et al, 2020;Fu et al, 2021;Yang et al, 2021) we included in the study based on the inclusion criteria, they all looked for potential survival-related OS gene signatures from public datasets.However, after we validated them in the training and validation cohorts, we found that the nine-gene signature we generated was superior to others in predicting OS prognosis. Among the nine studies, the one by Yang et al (2021)revealed a gene signature that closely resembled ours.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is relatively little success of immunotherapy in OSA patients to date, based on the tumor microenvironment profile it is suggested that OSA might be receptive to immune-therapies [13]. Recent articles on the immuno-genomic landscape in human OSA have sought to identify prognostic markers and genomic targets for immune therapy [14,15]. It has been shown that expression of PD-L1 in human OSA was significantly associated with number of immune infiltrates such as T cells, dendritic cells, and natural killer cells [16].…”
Section: Introductionmentioning
confidence: 99%